Concurrence of chronic lymphocytic leukaemia/small lymphocytic lymphoma and acute myeloid leukaemia in a bone marrow biopsy - Licci, Stefano (Polish Journal of Pathology, 2020)
The association of small lymphocytic lymphoma/chronic lymphocytic leukaemia (CLL) with different malignancies has been reported in the literature. Also the occurrence of a second haematological disease has been described, more frequently as a secondary event in patients receiving chemotherapeutic agents. We report a case of CLL with concurrent acute myeloid leukaemia in an untreated patient, with emphasis on the need of a detailed immunomorphological study to identify the coexistence of the two diseases in the same pathological tissue.